Social organization forms and institutional dynamics in the Tapajós-Arapiuns Reserve, state of Pará, Brazil - Andrade, Marcelo Moraes de; Silva, Danielle Wagner (Sustainability in Debate, 2019)
In this text, we will discuss the interdependence in processes that influence, directly or indirectly, the conditions of natural resources’ appropriation and list social interactions that will draw corresponding institutional frameworks to which dwellers of the Tapajós-Arapiuns Extractive Reserve will affiliate. The research that supports this paper has a multidisciplinary character, relying on the usage of various tools for obtaining information. The analytical notion of institutions (formal and informal rules) has been used to reference the developed interpretations. The considered object of analysis reflects over practices in the dwellers’ way of life, taking into account the alternatives of correlation between social organization and production practices. It is perceived that dwellers’ social frameworks of organization were constructed, not only by traditional institutional apparatus, but also by using coordination instruments and landuse planning, to manage common resources. These principles create an institutional order based on a presumed rationality, with distinct unfoldings and social impacts.